2020
DOI: 10.1007/s00167-020-06245-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliable improvements in participation in low-impact sports following implantation of a patellofemoral inlay arthroplasty at mid-term follow-up

Abstract: The aim of this study was, to investigate the rate of return to sports (RTS) and physical activity after implantation of PFIA and to identify factors predictive of improved postoperative sporting ability. Methods Sixty-two patients with a mean age of 46 ± 11 years, who underwent implantation of PFIA at the senior authors' institution, were enrolled. They were prospectively evaluated preoperatively and at a minimum of 2 years postoperatively with a mean follow-up of 60 ± 25 months. Clinical outcomes, return to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Foote et al found that only 54% of patients undergoing PFA with a second-generation implant were able to return to work 80 . Conversely, Pogorzelski et al reported that 94% of patients who did not fail could return to the same or higher level of sports, with 74% reporting an improved ability to perform low-impact sports 81 . This again highlights the importance of expectation management because it seems unlikely that most patients will return to high level or high-impact sports after PFA.…”
Section: Resultsmentioning
confidence: 99%
“…Foote et al found that only 54% of patients undergoing PFA with a second-generation implant were able to return to work 80 . Conversely, Pogorzelski et al reported that 94% of patients who did not fail could return to the same or higher level of sports, with 74% reporting an improved ability to perform low-impact sports 81 . This again highlights the importance of expectation management because it seems unlikely that most patients will return to high level or high-impact sports after PFA.…”
Section: Resultsmentioning
confidence: 99%
“…Another weakness is the retrospective type of the majority of the included studies, which could have led to an unknown selection bias. Another important aspect is that there are no studies reporting at mid-and long-term follow ups regarding the new inlay type of prosthesis, meaning that safe conclusions, with regards to the clinical and functional [38] 16 HemiCap Wave 24.1 (6-34) 1 (6.3%) 0 (0.0%) Metcalfe [32] 558 Avon 180 (nm) 61 (10.9%) 61 (10.9%) Ajnin [2] 43 FPV 65 (30-119) 5 (11.6%) 6 (13.9%) Bohu [10] 30 Hermes 240 (nm) 9 (30.0%) 9 (30.0%) Imhoff [22] 24 HemiCap Wave 60 (nm) 0 (0.0%) 6 (25.0%) Rammohan [42] 103 Journey 60 (± 12, 24-108) 9 (8.7%) 2 (1.9%) Bernard [7] 153 Avon 60 (± 30) 9 (5.9%) 9 (5.9%) Pogorzelski [40] 62 HemiCap Wave 60 (± 25) 12 (19.4%) 12 (19.4%) Marullo [30] 120 Gender Solutions 84 (± 30, 24-142) 5 (4.2%) 1 (0.8%) outcomes, and the survivorship of this type of prosthesis should be drawn with all due caution. Lastly, many authors were consultants for the companies designing the type of prostheses investigated in the respective studies, which might have led to a conflict of interest.…”
Section: Discussionmentioning
confidence: 99%
“…6 Comparison of the Physical Activity Scores between PFA and TKA groups Fig. 7 Forest plot of reporting satisfaction rates for PFA and TKA patients over a 3-to 17-year follow-up [43][44][45][46][47]. For example, Cartier et al [44] reported on a study of the firstgeneration of PFA that 55 of 65 patients achieved good to excellent results at 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Van der List JP et al [47] found that the 5-, 10-, 15-and 20-year survival rate of PFA prosthesis was 91.7%, 83.3%, 74.9%, and 66.6%, respectively. In addition, in a study of 62 patients with a mean follow-up of 5.0 ± 2.1 years, Jonas Pogorzelski et al [46] demonstrated that 94% of the patients with PFA were able to return to the same or higher level of exercise, while 74% of the patients showed improved ability to perform sports.…”
Section: Discussionmentioning
confidence: 99%